The use of CAM by women suffering from nausea and vomiting during pregnancy - Smith Michael; Georgousis Alexia; Boon Heather; Hollyer Taras; Einarson Adrienne (BMC, 2002)
Abstract Background Nausea and vomiting during pregnancy (NVP) affects two-thirds of pregnant women to varying degrees and over the years many modalities have been used to try to alleviate this often debilitating condition. There is a paucity of information in the literature about the use or efficacy of complementary and alternative medicine (CAM) for the treatment of this condition that affects so many women. Our primary objective was to examine the prevalence of CAM usage by women suffering from NVP. Our secondary objective was to ascertain if women had any supervision in the use of these treatments. Methods Women who called The Motherisk NVP helpline, were asked after the counseling session to complete a questionnaire, which included demographic data as well as information about their CAM use. Results Seventy women completed the questionnaire. 61% reported using CAM therapies, of which the three most popular were: ginger, vitamin B6 and acupressure. 21% of those who reported using CAM, had consulted CAM practitioners, 8% their physicians or pharmacists and 71% discussed the usage with family, friends and other allied health professionals. Women who did not use CAM stated they would probably use these modalities if there was more information about the safety in pregnancy. Conclusion Pregnant women with NVP are mirroring the trend in the general population of the use of CAM. They are also using CAM therapies with little supervision from practitioners experienced in the use of these modalities.